Clinical Correlations - Moore, Sean (Thrombosis and Haemostasis, 1975)
There are two aspects which are clinically relevant in the relationships among thrombosis and arteriosclerosis. First, the relationship of thrombosis to atherogenesis. Thrombosis is closely related to endothelial injury and there is recent evidence that repeated or continuous endothelial damage leads to the development of all the lesions seen in human atherosclerosis. This occurs in the absence of dietary lipid supplement. The relative importance of the parts played by injury and thrombosis in this process need further delineation. Secondly, established arteriosclerotic disease is associated with thrombosis. This thrombosis is usually mural, seldom occlusive. Embolism by platelet aggregates which has been well described in the retinal and cerebral circulations may affect other vascular territories such as the heart and the kidney. Such a mechanism may explain some cases of otherwise unexplained sudden cardiac death and some cases of hypertension. We need better clinical tools to detect the occurrence of thrombo-embolism and to monitor it’s progress. Measures to modify thrombosis and embolism may be as useful or more useful than those we currently employ in the clinical management of atherosclerotic disease.